PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ANDROID - Ir. Machudor Yusman (Jurnal Teknologi dan Informatika (JEDA), 2020)
AbstractMathematics education in elementary schools is very important, because it is the basis of the use of mathematics at the next level. The notion of mathematics as a frightening lesson must be eliminated and replaced with a pleasant lesson. In elementary schools most of the subject matter is delivered conventionally. So the material looks less attractive. For this reason, a learning innovation is needed so that the material looks more interesting and motivates students to learn. Especially the basic geometrical building calculation operations most frequently studied by elementary school students are calculating the area, perimeter, and volume of basic geometric shapes.This study aims to optimize the use of smartphones, especially Android in the world of education. T Pengembangan Media Pembelajaran Matematika Berbasis Androidhe method used by the author in the design of this application is the Waterfall method because this method is a structured approach, this research certainly there are still many shortcomings and things that still need to be studied and developed again.